Multi‐sectoral flexibility measures to facilitate wind and solar power integration - Juha Kiviluoma; Ciara O'Dwyer; Jussi Ikäheimo; Rinalini Lahon; Ran Li; Dana Kirchem; Niina Helistö; Erkka Rinne; Damian Flynn (IET Renewable Power Generation, 2022)
Abstract As power systems evolve towards integrating higher shares of renewables, the demand for additional levels of flexibility is increased. Meanwhile, o‐ther energy consuming sectors, such as transport and heating, could provide flexibility when they move from fossil fuels to electricity. In this paper, the impact of a range of flexibility measures is assessed for the island system of Ireland, with a high share of renewable energy, particularly wind and solar. Flexibility measures studied include hybrid heating in domestic and industrial processes, smart charging of electric vehicles, renewable hydrogen, power to ammonia, peak shaving demand response and batteries. The novelty of this paper lies in directly quantifying the interactions and dependencies between different flexibility measures, with the objective of increasing the operational flexibility of an increasingly renewable energy‐dominated power system. Four different scenarios are modeled to explore this interplay between the different flexibility measures. The costs and benefits of several sector‐coupling measures. The scenarios have also been compared in terms of their influence on system inertia, renewable energy curtailment and non‐synchronous penetration levels. The results indicate the potential importance of electricity‐based heating in the industrial sector, smart charging of electric vehicles, batteries and power‐to‐ammonia, as part of achieving future targets